2017
DOI: 10.1002/ieam.1916
|View full text |Cite
|
Sign up to set email alerts
|

Sources and dispersive modes of micro‐fibers in the environment

Abstract: Understanding the sources and distribution of microfibers (MFs) in the environment is critical if control and remediation measures are to be effective. Microfibers comprise an overwhelming fraction (>85%) of microplastic debris found on shorelines around the world. Although primary sources have not been fully vetted, until recently it was widely believed that domestic laundry discharges were the major source. It was also thought that synthetic fibers and particles having dimensions <5 mm easily bypassed filtra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
110
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(117 citation statements)
references
References 22 publications
3
110
0
4
Order By: Relevance
“…we would have expected a higher proportion of microplastics, but the proportions remained 473 relatively stable and we did not see any trends in our relatively small sample size. Interestingly, 474 our results are similar to the current global production of textile fibers at 60% synthetic fibers, 475 30% cotton and 10% other material (Carr, 2017). The study shows a significant number of 476 particles make their way to the open ocean and higher latitudes, where degradation rates may be 477 This study successfully harnessed the power of citizen science to collect high-quality data on a 503 global scale.…”
supporting
confidence: 63%
“…we would have expected a higher proportion of microplastics, but the proportions remained 473 relatively stable and we did not see any trends in our relatively small sample size. Interestingly, 474 our results are similar to the current global production of textile fibers at 60% synthetic fibers, 475 30% cotton and 10% other material (Carr, 2017). The study shows a significant number of 476 particles make their way to the open ocean and higher latitudes, where degradation rates may be 477 This study successfully harnessed the power of citizen science to collect high-quality data on a 503 global scale.…”
supporting
confidence: 63%
“…Microplastic fibers (to be referred to as microfibers; MFs) outnumber other types of microplastics, accounting for over 90% in some areas [2]. Worldwide, 9 million tons of fibers were produced in 2016, 60% of which were synthetics such as polyester, acrylic, polypropylene, and nylon [3]. The synthetic fibers used to make textiles (e.g., clothing, upholstery, and rugs) shed MFs during washing and regular use; a single garment can shed over 1,900 MFs per wash [4].…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic fibers used to make textiles (e.g., clothing, upholstery, and rugs) shed MFs during washing and regular use; a single garment can shed over 1,900 MFs per wash [4]. MFs enter the aquatic environment via sewage release, stormwater runoff, or atmospheric deposition [3,[5][6][7] where they accumulate and impact biota [8]. Polyester (PES) and polypropylene (PP) are the most commonly used a1111111111 a1111111111 a1111111111 a1111111111 a1111111111 (Ted Pella, Redding, CA) into MFs and stored in a clean glass bottle until use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that washing machines can generate over 1,900 plastic fibres in the single cycle (Browne et al 2011). The amount of microfibres will continue to increase in the future, and the only way to stop this is to avoid or improve the biodegradability of polymers used in textiles (Carr 2017). The appearance of microplastics in sewage sludge, on the one hand, is being reduced because of the effective treatment of sewage and concomitant reduction in the amount found in environments, yet remains a further threat because sewage sludge is commonly used for agricultural fertilization (Dris et al 2015b, Westphalen & Abdelrasoul 2018.…”
Section: Introductionmentioning
confidence: 99%